1995
DOI: 10.1172/jci117657
|View full text |Cite
|
Sign up to set email alerts
|

On the role of phosphatidylethanolamine in the inhibition of activated protein C activity by antiphospholipid antibodies.

Abstract: Phosphatidylethanolamine (PE) is an important membrane component for supporting activated protein C anticoagulant activity but has little influence on prothrombin activation. This difference constitutes a potential mechanism for selective inhibition of the protein C anticoagulant pathway by lupus anticoagulants and/or antiphospholipid antibodies. In this study, we demonstrate that the presence of PE augments lupus anticoagulant activity. In the plasma of some patients with lupus anticoagulants, activated prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
2
1

Year Published

1999
1999
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(106 citation statements)
references
References 30 publications
3
100
2
1
Order By: Relevance
“…Our previous studies indicated the importance of PE and polyunsaturation in the expression of APC activity (6,8,49). The studies reported here indicate yet another feature that distinguishes procoagulant from anticoagulant phospholipid surfaces.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Our previous studies indicated the importance of PE and polyunsaturation in the expression of APC activity (6,8,49). The studies reported here indicate yet another feature that distinguishes procoagulant from anticoagulant phospholipid surfaces.…”
Section: Discussionsupporting
confidence: 56%
“…The Effect of Patient Immunoglobulin on APC ActivityPreviously we showed that plasma or immunoglobulin derived from at least a subset of lupus patients could inhibit APC function selectively in a PE-dependent manner (37,49). Screening of IgG from several patients with thrombosis and APA or lupus anticoagulant indicated the anticoagulant activity of APC was inhibited more effectively on oxidized phospholipid than on nonoxidized phospholipid (data not shown).…”
Section: Effect Of Lipid Oxidation On Apc Anticoagulant Function-mentioning
confidence: 92%
“…The PLs 1,2-dilinoleoylsn-glycero-3-phosphatidylethanolamine (PE), 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphatidylserine (PS), and 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphatidylcholine (phosphatidylcholine) were purchased from Avanti Polar Lipids (Alabasta, AL). The PL liposomes were prepared by ultrasonication of a 1 mg/ml mixture of 40% PE, 20% PS, and 40% phosphatidylcholine in TBS (15).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the effects of APC-reactive mAb on APC activity in terms of plasma coagulation were examined according to the method described by Smirnov et al (15), with minor modifications. Experiments were conducted using TBS containing 0.1% gelatin in microtiter plates at 25°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation